Qualidade de vida e transporte público urbano: estratégias para melhorar a qualidade do serviço de transporte público urbano por ônibus - Amouzou, Koffi Djima (2000)
If urban planning is to support the equitable distribution of public goods and services, it must recognize and address the dismal condition of millions of poor people who are living in a city. The primary focus of contemporary planners and planning students should be on finding and advocating solutions that help eliminate the problems of today¿s cities. Any meaningful solution will need to be grounded in a thorough understanding of the social class inequities of citizens. With the rapid development of national economy and urbanization process in Brazil over the last two decades, the number of vehicles and their travels are dramatically increased. This is particularly evident in all large cities. Traffic congestion becomes more and more severe. Inadequate parking facilities often result in difficulty to find a parking space in large cities and many illegally parked vehicles can be seen on the crowed streets. These illegally parked vehicles further intensify traffic congestion and also pose a traffic safety hazard. The process of urbanization and motorization in Brazil is likely to continue in a rapid pace. The urban public passengers transport modes problems in large cities are likely to get even worse. There is an urgent need for the development of policy and criteria for public service of urban public passenger transport by bus in large cities. The purpose of survey is to develop policy guidelines for public transport services planning, design, construction and mobility management, that meet community needs for accessibility in large cities. So this thesis will present major comparative characteristics of urban mobility management, urban public passengers transport by bus services planning and the quality of social life in two towns of Brazil: Rio de Janeiro and Curitiba. The study case has been focused on Rio de Janeiro and Curitiba because of the major different results of the survey presented by the two cities. The objectives of this thesis are: a) to analyze and discus existing urban mobility related accessibility and economic development problems in large cities; b) to provide an overview of the relationship within city ¿ quality of social life ¿ urban mobility in Rio and Curitiba; c) to analyze and discuss existing urban mobility management related public transport services in Rio and Curitiba; d) to analyze and discuss existing quality of bus public transport services problems in Rio. Some preliminary recommendations for mobility management policies will also be presented.